Математична модель електромережі дільниці шахти у змінних стану - Сивокобиленко, В.Ф.; Василець, С.В. (Технічна електродинаміка, 2012)
The mathematical model of the mine power network was founded using the state variables method, which enables to analyse transients going with commutations of power connections, equiped by induction motors, and emergency states. The model is realized as application computer program with graphical interface, that simplifies structure and parameters definition for specified power network, coefficients of matrix differential state equation calculation and its numerical solving.